Makna dan Nilai Tuturan Sasaok Pada Masyarakat Rote - Ronni Marthen Ndun; Ona Diana Bani (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2021)
This study aims to identify, interpret and describe in order to obtain a clear picture of the meaning and value contained in the sasaok speech by using cultural linguistic theory and qualitative descriptive methods. The Sasaok traditional ceremony for the Rote community is a series of very sacred processes that must be passed by each prospective husband and wife which includes the lu'u inak stage (introductory stage), the natane inak stage (proposal stage), the nggani eik stage (confirmation stage) and the mbeda dode stage (intermediate stage) where each stage has its own speech and has meaning and value that must be maintained and respected by every married couple that is legalized by custom and cannot be separated except death.